A preliminary study on the learning perspective at Malaysia's government technical - Zainal Abidin, Noor 'Ain (2015)
A project manager is responsible for the successful project delivery. The project manager needs to effectively manage his team and all resources, in order to ensure the project is completed within the constraint of cost, schedule and quality, and also meeting the client’s satisfaction. Looking at project complexity nowadays, the project manager and project team member are required to acquire new knowledge and develop new skill from time to time. Time is not a privilege as ones handle more than one project at one time. Hence, the objectives of the study are to investigate their perspective towards learning and their perception on organizational support on learning. The study was conducted at a Malaysia’s Government technical department located in Klang Valley. 340 questionnaires were distributed and the rate of responses was about 53%. It was a quantitative approach and the analysis is mainly descriptive. The study demonstrated that all respondents realize the importance of learning and they are motivated to learn. They also perceived that there is organizational support towards learning, thus create a learning culture in the organization. Future studies should be undertaken to address the issue of what is the appropriate learning approach to enhance project management learning.